Influential Components in Financial Fraud Commission: Accountancy Professionals Perception - Díaz Agudelo, Valentina; Osorno Gallego, María Clara; Tangarife Gómez, Laura; Chamorro González, Candy (Semestre Económico, 2021)
Financial fraud affects the accounting profession, deteriorating society’s confidence in it and public faith. This research seeks to identify components that influence the development of financial fraud by Public Accountants and determine what strategies contribute to its mitigation. The methodology is qualitative with a descriptive scope and deductive method, documentary research and interviews are used to obtain opinions from professionals related to the problem. The results identified that the most common components are opportunity, pressure, and rationality; in addition to the absence of social conscience, power and low work motivation. Finally, it is concluded that the strategies that help to mitigate fraud in organizations are located in the academic, professional and research environment. Therefore, professional ethics and control bodies should be strengthened and more projects on the subject should be promoted.